Mitochondrial energy metabolism in heart failure: a question of balance - Huss, Janice M. (American Society for Clinical Investigation, 2005)
The mitochondrion serves a critical role as a platform for energy transduction, signaling, and cell death pathways relevant to common diseases of the myocardium such as heart failure. This review focuses on the molecular regulatory events and downstream effector pathways involved in mitochondrial energy metabolic derangements known to occur during the development of heart failure.